Nitric Oxide-Mediated Plasticity of Interconnections Between T-Stellate cells of the Ventral Cochlear Nucleus Generate Positive Feedback and Constitute a Central Gain Control in the Auditory System - Cao, Xiao-Jie; Lin, Lin; Sugden, Arthur U.; Connors, Barry W.; Oertel, Donata (The Journal of neuroscience, 2019)
T-stellate cells in the ventral cochlear nucleus (VCN) form an ascending pathway that conveys spectral information from the cochlea to brainstem nuclei, the inferior colliculi, and the thalamus. The tonotopic array of T-stellate cells enhances the encoding of spectral peaks relative to their auditory nerve fiber inputs. The alignment of local collaterals and T-stellate cell dendrites within the isofrequency lamina suggests that the cells make connections within the isofrequency lamina in which they reside. Recordings from pairs of T-stellate cells in mice of both sexes revealed that firing in the presynaptic cell evoked responses in the postsynaptic cell when presynaptic firing was paired with depolarization of the postsynaptic cell. After such experimental coactivation, presynaptic firing evoked EPSCs of uniform amplitude whose frequency depended on the duration of depolarization and diminished over minutes. Nitric oxide (NO) donors evoked EPSCs in T-stellate cells but not in the other types of principal cells. Blockers of neuronal nitric oxide synthase (nNOS) and of NMDA receptors blocked potentiation, indicating that NO mediates potentiation. nNOS and its receptor, guanylate cyclase (NO-GC), are expressed in somata of T-stellate cells. Excitatory interconnections were bidirectional and polysynaptic, indicating that T-stellate cells connect in networks. Positive feedback provided by temporarily potentiated interconnections between T-stellate cells could enhance the gain of auditory nerve excitation in proportion to the excitation, generating a form of short-term central gain control that could account for the ability of T-stellate cells to enhance the encoding of spectral peaks. T-stellate cells are interconnected through synapses that have a previously undescribed form of temporary, nitric oxide-mediated plasticity. Coactivation of neighboring cells enhances the activation of an excitatory network that feeds back on itself by enhancing the probability of EPSCs. Although there remain gaps in our understanding of how the interconnections revealed in slices contribute to hearing, our findings have interesting implications. Positive feedback through a network of interconnections could account for how T-stellate cells are able to encode spectral peaks over a wider range of intensities than many of their auditory nerve inputs (Blackburn and Sachs, 1990; May et al., 1998). The magnitude of the gain may itself be plastic because neuronal nitric oxide synthase increases when animals have tinnitus (Coomber et al., 2015).